ThreadSafe: Static Analysis for Java Concurrency - Atkey, Robert; Sannella, Donald (Electronic Communications of the EASST, 2015)
ThreadSafe is a commercial static analysis tool that focuses on detection of Java concurrency defects. ThreadSafe’s bug-finding capabilities and its look and feel are presented through examples of bugs found in the codebases of two widely-used open source projects.